The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1074/jbc.ra118.005092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of membrane-bound sulfane reductase: A missing link in the evolution of modern day respiratory complexes

Abstract: Hyperthermophilic archaea contain a hydrogen gas-evolving,respiratory membrane-bound NiFe-hydrogenase (MBH) that is very closely related to the aerobic respiratory complex I. During growth on elemental sulfur (S°), these microorganisms also produce a homologous membrane-bound complex (MBX), which generates HS. MBX evolutionarily links MBH to complex I, but its catalytic function is unknown. Herein, we show that MBX reduces the sulfane sulfur of polysulfides by using ferredoxin (Fd) as the electron donor, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…saccharovorans (Mardanov et al ., ), were identified in both Acidilobus MAGs as well as the Thermoproteus , Caldimicrobium , Caldivirga , Vulcanisaeta , Desulfurococcales, Thermofilum , Thaumarchaeote Bin14 and both Fervidicoccus MAGs. In addition, homologues of a membrane‐bound oxidoreductase (Mbx), which is involved in reducing the persulfide bond in S x 2− in Pyrococcus furiousus (Wu et al ., ), were identified in the Thermogladius MAG. Based on (i) a lack of detected homologues for key enzymes involved in each of the four primary autotrophic pathways, (ii) the detection of homologues of for complete (or nearly complete) TCA and glycolytic pathways and (iii) the detection of homologues of carbohydrate, polypeptide or amino acid transporters, the Acidilobus , Thermogladius , Caldivirga , Vulcanisaeta , Desulfurococcales, Thaumarchaeote and Fervidicoccus‐ related MAGs are inferred to be heterotrophic.…”
Section: Resultsmentioning
confidence: 99%
“…saccharovorans (Mardanov et al ., ), were identified in both Acidilobus MAGs as well as the Thermoproteus , Caldimicrobium , Caldivirga , Vulcanisaeta , Desulfurococcales, Thermofilum , Thaumarchaeote Bin14 and both Fervidicoccus MAGs. In addition, homologues of a membrane‐bound oxidoreductase (Mbx), which is involved in reducing the persulfide bond in S x 2− in Pyrococcus furiousus (Wu et al ., ), were identified in the Thermogladius MAG. Based on (i) a lack of detected homologues for key enzymes involved in each of the four primary autotrophic pathways, (ii) the detection of homologues of for complete (or nearly complete) TCA and glycolytic pathways and (iii) the detection of homologues of carbohydrate, polypeptide or amino acid transporters, the Acidilobus , Thermogladius , Caldivirga , Vulcanisaeta , Desulfurococcales, Thaumarchaeote and Fervidicoccus‐ related MAGs are inferred to be heterotrophic.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Indeed, a recent study identified a membrane bound oxidoreductase, termed MBX (Schut et al 2007;Wu et al 2018), that is involved in reduction of sulfane bonds during Sx 2− reduction in the hyperthermophile P. furiousus. Thus, Sx 2− is likely the soluble intermediate for S° reduction for microorganisms growing at pH >6.0 (Findlay 2016;Schauder and Muller 1993).…”
Section: Mechanism Of S Reduction Oxidation and Disproportionation mentioning
confidence: 99%
“…This has led to the suggestion that MBX represents an evolutionary "intermediate" between early evolving H2 based respiratory metabolisms and those using oxidants with much higher potential (Boyd et al 2014;Schut et al 2016). Neutrophilic hyperthermophiles, such as Pyrococcus and Thermococcus, use MBX to reduce the sulfane bonds in SX 2- (Wu et al 2018). Homologs of MBX have also been identified in a variety of crenarchaeotes that commonly inhabit hot spring environments, including a variety of neutrophilic members of the Desulfurococcales (Schut et al 2013).…”
Section: Consistent With This Model Similar Growth Experiments With mentioning
confidence: 99%
“…The energy production strategies supporting growth of hyperthermophilic archaea push the known limits of energy-conserving mechanisms (17). Although fermentation of peptides and sugars permits net ATP production, many hyperthermophiles are reliant on additional ATP production through the action of respiratory complexes for rapid and efficient growth (815). If reduction of even weakly energetic substrates can be coupled to formation of an electrochemical gradient, this gradient can be exploited for ATP production (1618).…”
Section: Introductionmentioning
confidence: 99%
“…kodakarensis utilizes a modified Embden-Meyerhof (EM) pathway wherein glycolysis results in modest net gains in ATP production (1, 8, 10, 3639). Cellular growth is dependent on membrane-bound respiratory complexes that use reduced Fds (Fd red ) to generate electrochemical ion gradients that are exploited for additional ATP production (5, 9, 10, 14, 15, 40, 41). Fd red not only act as temporary carriers of valuable electrons to membrane-bound complexes that couple the exergonic transfer of electrons to the simultaneous translocation of ions across the cellular membrane, but also shuttle electrons to soluble ferredoxin:NAD(P)H oxidoreductases that generate NAD(P)H (42) or reductases involved in isoprenoid-based lipid production (43).…”
Section: Introductionmentioning
confidence: 99%